LINC01116 Promotes Doxorubicin Resistance in Osteosarcoma by Epigenetically Silencing miR-424-5p and Inducing Epithelial-Mesenchymal Transition - Li, Ran; Ruan, Qing; Zheng, Jia; Zhang, Butian; Yang, Hongliang (Frontiers in Pharmacology, 2021)
Background: Development of resistance to doxorubicin-based chemotherapy limits its curative effect in osteosarcoma. In the current study, we focused on investigating the mechanisms underlying the development of doxorubicin resistance in osteosarcoma. Methods: The human osteosarcoma cell line MG-63 and doxorubicin-resistant MG-63/Dox cells were used in this study. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the expression of the long non-coding RNA LINC01116 in the two cell lines. Then, the specific shRNA for LINC01116 was employed to suppress LINC01116 expression in MG-63/Dox cells. Cell viability was assessed by the CCK-8 and colony formation assays. Cell migration and invasion were evaluated by the transwell assay. Moreover, the epithelial-mesenchymal transition (EMT)-related proteins, E-cadherin, vimentin, and N-cadherin were evaluated by Western blotting. The regulation of LINC01116 on miR-424-5p expression was examined using methylation-specific PCR, RNA immunoprecipitation, and Western blotting assay. The potential targeting of HMGA2 by miR-424-5p was predicted using the bioinformatics databases TargetScan and miRanda and verified by a dual-luciferase reporter assay. Results: LINC01116 was more highly expressed in MG-63/Dox cells than in MG-63 cells. Inhibition of LINC01116 suppressed cell viability, migration, and invasion, along with upregulating the expression of E-cadherin, downregulating vimentin, and attenuating doxorubicin resistance in MG-63/Dox cells. Further mechanism-related investigations indicated that LINC01116 regulated HMGA2 expression via the EZH2-associated silencing of miR-424-5p. Conclusion: LINC01116 exerts regulatory effects on doxorubicin resistance through the miR-424-5p axis, providing a potential approach to overcoming chemoresistance in osteosarcoma.